2013
DOI: 10.1016/j.freeradbiomed.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase regulates acrolein-induced cytotoxicity in human small airway epithelial cells

Abstract: Aldose reductase (AR), a glucose metabolizing enzyme, reduces lipid aldehydes and their glutathione conjugates with more than 1000-fold efficiency (Km aldehydes 5-30μM) than glucose. Acrolein, a major endogenous lipid peroxidation product as well as component of environmental pollutant and cigarette smoke, is known to be involved in various pathologies including atherosclerosis, airway inflammation, COPD, and age-related disorders but the mechanism of acrolein-induced cytotoxicity is not clearly understood. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Our previous report demonstrated that IL‐17A‐mediated EMT occurs via TGF‐β1‐dependent signaling, particularly p38MAPK activation (22), and p38MAPK has been implicated in epithelial injury (32). However, the correlation between TGF‐β1‐mediated p38MAPK activation and complement activation‐mediated epithelial injury is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous report demonstrated that IL‐17A‐mediated EMT occurs via TGF‐β1‐dependent signaling, particularly p38MAPK activation (22), and p38MAPK has been implicated in epithelial injury (32). However, the correlation between TGF‐β1‐mediated p38MAPK activation and complement activation‐mediated epithelial injury is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…p38MAPK has been widely implicated in epithelial injury (22, 32, 41). Accordingly, we observed a role of p38MAPK in protecting against the loss of CIPs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other reactive carbonyl species, acrolein is highly reactive with cellular nucleophiles such as proteins, DNA, and RNA. Acrolein readily targets and reacts with sulfhydryl or thiol groups and consequently depletes reduced glutathione (GSH), thioredoxin, and glutaredoxin, which are important antioxidants, therefore, there is increased oxidative stress [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Acrolein readily targets and reacts with the sulfhydryl group of cysteines to form thioether adducts via a Michael addition mechanism [8]. Depletion of cellular reduced glutathione (GSH) by the formation of GS-acrolein conjugates results in increased oxidative stress [9][10][11]. Acrolein can also deplete protein thiols, such as thioredoxin and glutaredoxin, which are important antioxidant proteins [12,13].…”
Section: Introductionmentioning
confidence: 99%